Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.ultrasmedbio.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between 360° 3-D Transvaginal Ultrasound and Magnetic Resonance Imaging for Assessment of Vaginal Invasion in Cervical Cancer: A Preliminary Report

Abstract: Our goal was to estimate the agreement between 360˚3-D transvaginal ultrasound (TVUS) and magnetic resonance imaging (MRI) of the vaginal invasion in cervical cancer and to discuss the clinical value of 3603 -D TVUS. A total of 72 patients with untreated cervical cancer were included in the work. The percentage agreement between 2-D TVUS and MRI in assessing vaginal invasion (yes or no) was 77.8% (kappa, 0.400) and that between 360˚3-D TVUS and MRI was 97.2% (kappa, 0.873). The results of 2-D TVUS demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Unlike traditional intracavitary 3D volume reconstruction, 360°‐3D‐TVS uses a multifrequency 12–16‐MHz ring‐shaped single‐plane probe for scanning and 3D reconstruction, offering improved image resolution and detection of small lesions. Our previous research found that 360°‐3D‐TVS demonstrated good agreement with magnetic resonance imaging in assessing the extent of vaginal invasion in patients with cervical cancer 5 . It remains unknown whether 360°‐3D‐TVS can be used effectively to define vaginal lesions and their anatomical relationship with adjacent major organs.…”
Section: Parameter Anechoic Cystic Heterogeneous Cystic Hypoechogenic...mentioning
confidence: 99%
“…Unlike traditional intracavitary 3D volume reconstruction, 360°‐3D‐TVS uses a multifrequency 12–16‐MHz ring‐shaped single‐plane probe for scanning and 3D reconstruction, offering improved image resolution and detection of small lesions. Our previous research found that 360°‐3D‐TVS demonstrated good agreement with magnetic resonance imaging in assessing the extent of vaginal invasion in patients with cervical cancer 5 . It remains unknown whether 360°‐3D‐TVS can be used effectively to define vaginal lesions and their anatomical relationship with adjacent major organs.…”
Section: Parameter Anechoic Cystic Heterogeneous Cystic Hypoechogenic...mentioning
confidence: 99%